Sharing session: Utilization of waste into paper soap by students of Universiti Utara Malaysia, Malaysia - Susilo, Rinto; Indriaty, Sulistiorini; Setyaningsih, Indah; Santana, Salma Audhita; Listiyani, Lilis; Nufus, Hana Syifaun; Choerunnisa, Sari; Anoez, Nawaal Hilmy; Fadila, Fasiha Nur (Community Empowerment, 2025)
Handwashing is one of the simplest yet most unattainable actions for millions of families worldwide. In an effort to address this issue, a pharmaceutical preparation in the form of paper soap was introduced and the optimization of natural waste utilization into valuable products was carried out. The aim of this program is to improve healthy living behavior in a university environment. The community service program was implemented through a semi-formal sharing session at the UUM SAC Building for 40 non-health UUM students. The success of this activity can be seen from the increased average value of the pre-test and post-test. This indicates that participants' understanding has increased after the sharing session.